Isolated intense half-cycle attosecond pulse generation with orbital angular momentum. (12th January 2021) - Xu, Zhangli; Shen, Baifei; Zhang, Lingang; Xu, Jiancai; Gong, Weifeng
Abstract: A relativistic linearly polarized Laguerre–Gaussian (LG) laser pulse interacting with a combination of gas plasma and an oblique foil target is proposed to generate an intense attosecond pulse carrying large orbital angular momentum (OAM). The LG laser pulse firstly produces an ultra-thin relativistic electron sheet (RES) in underdense plasma and transfers the OAM to the latter at the same time. When the RES passes through the oblique foil, it radiates an intense half-cycle attosecond pulse carrying large OAM. Three-dimensional particle-in-cell simulation confirms that an isolated ultra-intense half-cycle attosecond pulse with a duration of 542 as and a peak electric field of 5 × 10 12 V m −1 is produced. The average OAM per photon of the attosecond pulse is about −1 ћ . Such an intense, isolated attosecond pulse with the large OAM would provide new possibilities in attosecond scientific research.